Shine a Light: How Firm Responses to Announcing Earnings Restatements Changed After Sarbanes–Oxley - Pozner, Jo-Ellen (Journal of business ethics, 2019)
We explore how the Sarbanes–Oxley Act of 2002 created pressure for firms to take more visible and costly corrective action following the announcement of an earnings restatement. Building on theory about focusing events, the institutional effects of legislative change, and the agenda-setting role of the media, we propose that Sarbanes–Oxley created reactive normative pressure on firms that announce earnings restatements, increasing the likelihood of CEO replacement in their aftermath. We theorize that Sarbanes–Oxley changed the meaning—and therefore the impact—of media coverage of earnings restatements. Our findings show that firm behavior after Sarbanes–Oxley did change in ways that are consistent with the intent of the legislation: to increase executives’ accountability for the reliability of their firms’ financial statements. Moreover, we show this change is a result both of the direct effect of the legislation on increasing CEO accountability as well as through intensifying the effect of the media spotlight on misconduct.